Meditative and Mindfulness-Focused Interventions in Neurology: Principles, Science, and Patient Selection - Kraemer, Kristen M.; Jain, Felipe A.; Mehta, Darshan H.; Fricchione, Gregory L. (Seminars in Neurology, 2022)
A growing body of research suggests that meditative- and mindfulness-focused interventions may improve neuropsychiatric symptoms that commonly occur in a range of neurological disorders. In this article, the principles of meditation and mindfulness are first defined, as well as briefly describing the neurobiological mechanisms implicated in these interventions. Thereafter, a range of meditative- and mindfulness-focused interventions are detailed, along with their supporting evidence to treat neuropsychiatric symptoms in neurological conditions (e.g., headache, movement disorders, chronic pain, etc.). Overall, these interventions warrant further investigation among individuals with neurological conditions. When recommending these interventions, health care professionals must consider a combination of structural (e.g., insurance reimbursement) and patient factors (e.g., ability to tolerate a group setting).
Keywords: meditation; mindfulness; mind–body; neurology